ANÁLISIS DEL CONSUMO INFANTIL DE TV, VIDEOJUEGOS E INTERNET: DIFERENCIAS EN FUNCIÓN DEL SEXO EN LA SELECCIÓN DE CONTENIDOS AUDIOVISUALES - Dra. Beatriz FEIJOO FERNÁNDEZ,Dra. Aurora GARCÍA GONZÁLEZ (Fonseca, Journal of Communication, 2023)
Under a strategy to attract diverse audiences, the audiovisual industry has been fragmenting its content based on several criteria, including the gender. In this sense, this research aims to verify if these distinctions are reflected in the children´s content selection in relation with different screens (TV, videogames and the internet). To cope with this research, we selected a quantitative analysis using the technique of the questionnaire that was distributed among students of 6th year primary school, who are between 11 and 12 years to finally access to a sample of 2200 individuals from 77 public and private Galician schools. Thanks to this data, we could corroborate that children choose completely different content according to their gender, excepting internet, media in which their preferences tend to converge.